Estranging the novel : Poland, Ireland, and theories of world literature - Bartoszynska, Katarzyna (Johns Hopkins University Press, 2021)
By modeling such a heterogeneous account of the novel form, Estranging the Novel paves the way for a bracing and diverse understanding of the makeup of contemporary world literature and the many texts it encompasses--and a new perspective on the British novel as well.